2021
DOI: 10.3390/foods10020380
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ripening on the Phenolic Composition and Mineral Content of Three Varieties of Olive Fruits

Abstract: The phenolic composition and mineral content of Cornezuelo, Cornicabra and Picual olive fruit varieties were investigated during olive ripening in two different harvesting seasons (2017/2018 and 2018/2019). Phytochemical profiles were evaluated by high-performance liquid chromatography (HPLC) with diode-array and mass spectrometry detection. Mineral contents were determined by inductively coupled plasma-mass spectrometry (ICP-MS). Twenty-five compounds were characterized and the main ones quantified. These com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…Minor chromatographic peaks were emphasized by magnifications reported in insets to panels b, c, d, e, and f of the figure. In agreement with previous findings [ 22 , 24 , 26 , 27 , 28 , 31 ], peaks related to isomeric forms were detected not only for oleuropein, but also for ligstroside and for demethylated oleuropein and ligstroside. Normalization Levels (NL) referred to the respective XIC traces suggested that demethylated forms were present at much lower concentrations ( vide infra ).…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…Minor chromatographic peaks were emphasized by magnifications reported in insets to panels b, c, d, e, and f of the figure. In agreement with previous findings [ 22 , 24 , 26 , 27 , 28 , 31 ], peaks related to isomeric forms were detected not only for oleuropein, but also for ligstroside and for demethylated oleuropein and ligstroside. Normalization Levels (NL) referred to the respective XIC traces suggested that demethylated forms were present at much lower concentrations ( vide infra ).…”
Section: Resultssupporting
confidence: 92%
“…Based on the similarity of the MS/MS fragmentation pathways, an additional peak, closer to that of oleuropein, was assigned as "oleuropein isomer" in three studies [25][26][27]. The presence of an isomeric form of oleuropein in extracts of drupes from different Spanish olive cultivars was recently reported also by Fernandez-Poyatos et al [31]. Additionally, some differences in the profiles of product ions obtained for oleuropein (and its putative isomer) and oleuroside were evidenced by Quirantes-Piné et al [27] after MS/MS analysis, yet an interpretation for this finding was not reported.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations